THE ROLE AND IMPORTANCE OF LIVESTOCK SECTORS IN AGRICULTURE - Olimov Qodirjan Qobiljan Ugli (Scholar Express Journals, 2021)
Livestock is an important component of agriculture in the country and is the second largest sector. Appropriate, effective placement and development of the livestock sector has a direct impact on the positive solution of the division of labor in the country. Taking into account the natural and economic conditions of the regions and market requirements, it is necessary to locate and develop cattle breeding, sheep breeding, astrakhan breeding, beekeeping and horse breeding. Because these industries produce meat, milk, wool, leather, intestines, honey and other products for the food and processing industries. As a result, the development of industries will be ensured. The livestock sector also grows a variety of products rich in protein, which are necessary for human health
Keywords: Livestock; human health; cattle breeding; sheep breeding